Swyer‐James syndrome associated with asthma and a giant bulla. Issue 4 (22nd October 2014) - Kayawake, Hidenao; Sakai, Hiroaki; Matsumoto, Hisako; Date, Hiroshi
Abstract Swyer‐James syndrome was first described in 1953 as unilateral pulmonary emphysema in a 6‐year‐old boy. The characteristic feature of this syndrome is unilateral pulmonary hyperlucency on a chest X‐ray film. Typical symptoms include recurrent chest infections, chronic cough, wheezing, and exertional dyspnea. Although there have been a few reports of pneumothorax in patients with Swyer‐James syndrome, there have been no reports about an association with giant bullae. Here, we report a case of Swyer‐James syndrome associated with a giant bulla and asthma, in which surgery achieved marked improvement of dyspnea.